The prism manifold realization problem III. Issue 4 (27th August 2022) - Ballinger, William; Ni, Yi; Ochse, Tynan; Vafaee, Faramarz
Abstract: Every prism manifold can be parametrized by a pair of relatively prime integers p > 1 p>1 and q q . In our earlier papers, we determined a complete list of prism manifolds P ( p, q ) P(p, q) that can be realized by positive integral surgeries on knots in S 3 S^3 when q < 0 q<0 or q > p q>p ; in the present work, we solve the case when 0 < q < p 0<q<p . This completes the solution of the realization problem for prism manifolds.